Penal Policy on Digital Defamation: A Comparative Study of Indonesian and Malaysian Law - Hartanto Hartanto; Syakdiah Syakdiah; Dwi Astuti; Daniil Alimpeev (Universitas Negeri Semarang, 2026)
The expansion of criminal defamation in digital space, particularly under Indonesia’s ITE Law, has raised concerns over disproportionate restrictions on freedom of expression compared to neighboring jurisdictions such as Malaysia. This study aims to examine how Indonesia and Malaysia regulate criminal defamation and to identify key differences in their penal policies. The central issue is whether reliance on criminal law as a primary regulatory instrument leads to disproportionate interference with freedom of expression in both jurisdictions. This research employs a normative juridical method with a comparative law approach, analyzing Article 27A of Law No. 1 of 2024 (ITE Law), the new Indonesian Criminal Code, and Sections 499–502 of the Malaysian Penal Code, complemented by the Defamation Act 1957 and Constitutional Court Decision No. 105/PUU-XXII/2024. The findings indicate three principal differences. Indonesia maintains a broader scope of criminalization with imprisonment as a dominant sanction, whereas Malaysia tends to prioritize civil remedies. Malaysia also demonstrates more developed defenses grounded in public interest. At the same time, Indonesia’s approach remains less structured in distinguishing legitimate criticism from defamation and in translating principles of reputation protection into proportional legal standards. The study concludes that Indonesia’s current framework risks over-criminalization and requires reform to ensure proportionality. Criminal sanctions should be applied as a last resort (ultimum remedium), supported by mandatory mediation and clearer normative boundaries.